LOPES, Twig Santos. 2024. Violência Política contra as Mulheres. Rio de Janeiro: Mórula. 272 p. - Mariah Torres Aleixo (Universidade do Estado do Rio de Janeiro, 2024)
Resenha: LOPES, Twig Santos. Violência Política contra as Mulheres. Rio de Janeiro: Mórula, 2024. 272